Direct enantio- and diastereoselective Mannich reactions of malonate and beta-keto esters with N-Boc and N-Cbz aldimines catalysed by a bifunctional cinchonine derivative. - Tillman, A; Ye, J; Dixon, D (2006)
A highly enantioselective Mannich reaction between malonate esters and N-Boc and N-Cbz aldimines, catalysed by a bifunctional cinchonine derivative, has been developed; extension of this methodology to encompass the use of 2-substituted-1,3-dicarbonyl nucleophiles allows the formation of adjacent stereocentres, one of which is quaternary, in high relative and absolute stereocontrol.